Detailed Implementation Review : India Health Sector, 2006-2007, Volume 2 - World Bank (Washington, DC, 2014)
This report summarizes the findings of a Detailed Implementation Review (DIR) of five Bank-financed projects in India: the Food and Drugs Capacity Building Project, the Orissa Health Systems Development Project; the Second National AIDS Control Project; the Malaria Control Project; and the Tuberculosis Control Project. The DIR is a strictly confidential internal World Bank document, the purpose of which is described herein. Its findings are of a highly sensitive and confidential nature and should not be used by the Government of India as the basis for initiating any administrative, criminal, or civil proceeding. The Government of India may wish to undertake its own investigation into matters raised by this DIR to determine whether any of the laws of India may have been violated. Moreover, the DIR should not be cited or referred to in the course of any Government of India investigation, in its investigation reports, or in any administrative, civil, or criminal proceedings undertaken by the Government of India related to the five projects reviewed in this report. This report is provided without prejudice to the World Bank s privileges and immunities.